1999
DOI: 10.1007/s001980050227
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Quantitative Ultrasound Measurements as Compared with Dual-Energy X-ray Absorptiometry in the Assessment of Corticosteroid-Induced Bone Impairment

Abstract: Bone loss due to corticosteroid treatment differs from that of postmenopausal osteoporosis with regard to bone structure. Corticosteroids affect both horizontal and vertical trabeculae while horizontal trabeculae are damaged in postmenopausal osteoporosis. Dual-energy X-ray absorptiometry (DXA) is the gold standard to evaluate bone loss. The place of quantitative ultrasound (QUS), a technique that could theoretically provide information on bone structure, is not well established in corticosteroid-induced bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 25 publications
0
15
1
2
Order By: Relevance
“…It is smaller than the 12.7% observed in a cohort of mixed inflammatory disorders using the Lunar Achilles [21]. The difference detected by QUS was greater in magnitude than that detected by calcaneal DXA; furthermore, adjusting calcaneal QUI for calcaneal DXA in a multivariate model did not appreciably reduce the difference between CS users and non-users.…”
Section: Discussioncontrasting
confidence: 66%
“…It is smaller than the 12.7% observed in a cohort of mixed inflammatory disorders using the Lunar Achilles [21]. The difference detected by QUS was greater in magnitude than that detected by calcaneal DXA; furthermore, adjusting calcaneal QUI for calcaneal DXA in a multivariate model did not appreciably reduce the difference between CS users and non-users.…”
Section: Discussioncontrasting
confidence: 66%
“…Indeed, in this study we found that BUA was reduced by 6.3%, SOS by 1.6% and SI by 15.8% compared with values obtained in control subjects. In the same manner Daens et al [9] showed that QUS measurements were decreased in patients with CIOP (75.8% for BUA, 71.3% for SOS and 712.7% for SI). However, in these two previous studies the decrease in QUS measurements in CIOP was similar to that of BMD LS .…”
Section: Discussionmentioning
confidence: 63%
“…In a recently published study we also showed that QUS parameters were decreased to the same extent as BMD in patients with CIOP due to exogenous glucocorticoid excess [8]. Also Daens et al [9] showed that the Stiffness Index (SI) was decreased by 12.7% (against 11% for BMD at the lumbar spine) in a group of patients receiving pharmacologic doses of steroids for more than 1 year. Nevertheless, to our knowledge QUS parameters of bone have not been assessed in endogenous corticosteroid excess.…”
Section: Introductionmentioning
confidence: 81%
“…Quantitative ultrasound evaluations at the heel and hand phalanges have also been investigated as a method of assessing bone loss in GC-treated patients [192,193] . The data are very limited at the present time, and more research is necessary to establish if quantitative ultrasound may be suitable for such a purpose in routine clinical practice.…”
Section: Bmd Assessmentmentioning
confidence: 99%